2019
DOI: 10.3390/cancers11101415
|View full text |Cite
|
Sign up to set email alerts
|

Sestrins as a Therapeutic Bridge between ROS and Autophagy in Cancer

Abstract: The regulation of Reactive Oxygen Species (ROS) levels and the contribution therein from networks regulating cell metabolism, such as autophagy and the mTOR-dependent nutrient-sensing pathway, constitute major targets for selective therapeutic intervention against several types of tumors, due to their extensive rewiring in cancer cells as compared to healthy cells. Here, we discuss the sestrin family of proteins—homeostatic transducers of oxidative stress, and drivers of antioxidant and metabolic adaptation—as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 151 publications
(191 reference statements)
0
30
0
Order By: Relevance
“…Redox homeostasis is also regulated by non-enzymatic proteins as SESNs or mitochondrial uncoupling proteins (UCPs). SESNs are a family of highly conserved stress-inducible proteins that are strongly up-regulated by oxidative stress as an antioxidant adaptive response [45,46]. During oxidative stress, their expression may be controlled from induced transcription factors, such as p53, Nrf2, or FOXO.…”
Section: Main Non-enzymatic Antioxidant Systems Involved In Tumor Promentioning
confidence: 99%
See 3 more Smart Citations
“…Redox homeostasis is also regulated by non-enzymatic proteins as SESNs or mitochondrial uncoupling proteins (UCPs). SESNs are a family of highly conserved stress-inducible proteins that are strongly up-regulated by oxidative stress as an antioxidant adaptive response [45,46]. During oxidative stress, their expression may be controlled from induced transcription factors, such as p53, Nrf2, or FOXO.…”
Section: Main Non-enzymatic Antioxidant Systems Involved In Tumor Promentioning
confidence: 99%
“…A recent report demonstrated that SESN2 can inhibit the pro-oxidant enzyme NADPH oxidase 4 (NOX4), preventing pathogenic amounts of cytosolic ROS [48]. SESNs may also contribute to redox homeostasis through the regulation of AMPK-mTORC1 signaling pathways, preventing mammalian target of rapamycin complex 1 (mTORC1) hyperactivation [49] which may enhance ROS production via inhibition of autophagy [50] or directly acting on mitochondrial function [46]. SESN-dependent inhibition of mTORC1 can be also important for autophagy-mediated degradation of Keap1, the inhibitor of Nrf2 [46].…”
Section: Main Non-enzymatic Antioxidant Systems Involved In Tumor Promentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, such regulation could be a potential target mechanism for cancer treatment. Based on this idea, Sanches-Ávarez et al [4] recognize the sestrin family of proteins as a "missing link" between ROS and autophagy in cancer cells. In their review "Sestrins as a Therapeutic bridge between ROS and Autophagy in Cancer", the authors discuss possibilities for the adaptive regulation of ROS-induced autophagy by sestrins.…”
mentioning
confidence: 99%